Investigação do efeito vasorelaxante e caracterização eletrofisiológica dos alcalóides curina e reticulina - Medeiros, Marcos Antônio Alves de (2009)
It was been demonstrated that curine and reticuline, induced a vasodilator effect in the rat small mesenteric arteries through inhibition of voltage-gated Ca2+ channels (VGCC). These compounds, curine and reticuline were isolated from the root barks of Chondrondendron platyphyllum and Ocotea duckei Vattimo, respectively, therefore the aim of this work was to evaluate the vasodilator mechanism of curine and reticuline, bisbenzylisoquinoline alkaloids (BBA), isolated from the root barks of Chondrondendron platyphyllum and Ocotea duckei Vattimo, respectively, using functional and molecular approaches. Tension measurements in aorta rings, whole-cell patch-clamp and confocal techniques were employed to study the action of these alkaloids. The A7r5 smooth muscle derived cell line was used for Ca2+ currents measuring and the intracellular calcium concentration ([Ca2+]i) were evaluated using confocal microscopy. The main results are as follows: in aortic rings, curine (3 - 300 μM) antagonized KCl (60 mM) and Bay K8644 (3 x 10-7 M) induced contractions. In whole-cell configuration, curine reduced the voltage-activated peak amplitude of ICa,L in a concentration-dependent manner. However, the Ca+2 current density versus voltage relationship and maximal activation voltage of ICa,L were not changed. Moreover curine did not also affect the steady-state activation of ICa,L, but shifted the steady-state inactivation curve of ICa,L for more negative potentials, however this effect was not changed in the presence of IBMX, dbcAMP and 8-brcGMP, suggesting that cyclic mononucleotides, such as cAMP and cGMP, are not involved in curine effect. In confocal experiments, curine inhibited the rise on the [Ca2+]i induced by KCl (60 mM) in dispersed vascular smooth muscle cells. In reference to reticuline (3 300 μM) was verified that alkaloid agonized CaCl2 and KCl-induced contractions and elicited vasorelaxation in aortic rings. In whole-cell configuration, reticuline reduced the voltage-activated peak amplitude of ICa,L in a concentration-dependent manner, but did not change the characteristics of current density versus. voltage relationship. Reticuline shifted leftwards the steady-state inactivation curve of ICa,L, however this effect was not changed after application of dibutyryl cyclic adenosine monophosphate to the cell. In cells pretreated with forskolin, an adenylate cyclase activator, the addition of reticuline caused further inhibition of the Ca2+ currents suggesting an additive effect, indicating that cyclic mononucleotides were not involved. Taken together the results have shown that curine and reticuline elicits vasorelaxation due to the blockade of the L-type voltage-dependent Ca2+ current in rat aorta smooth muscle cells. The reported effect may contribute to the potential cardioprotective efficacy of curine and reticuline.